Attracting international customer through mass media while keeping the sense of premium: Case study among Finnish premium and luxury brands - Lauri, Hanna (My University, 2019)
Even though social media has been a phenomenon for several years, there is no end in sight. For today’s consumers, social media plays a crucial role when familiarizing themselves with brands and products. Thus, the role of the social media is constantly growing in companies and its cost-effectiveness attracts especially small and medium-sized enterprises. Social media is creating opportunities for entrepreneurial marketing (EM) since the speed and reach across borders are attracting small entrepreneurs. It is essential to study, how small and medium-sized companies with limited resources can use social media as a tool to attract international customers. This study aims to explore how through social media value can be created in order to attract international customers in SME premium and luxury industry. The literature review of this study is based on an extensive amount of literature from the field of entrepreneurial marketing and social media marketing, taking also luxury and premium industry into consideration. Based on the literature review, the theoretical framework is conducted. This study has been executed as qualitative and exploratory study. The empirical data was collected through semi-structured interviews where three representatives of small and medium-sized SMEs operating in Finnish luxury and premium industry were interviewed. This study covers the gap between entrepreneurial marketing, luxury and premium industry and international social media marketing by providing insights on how social media can be utilized in this context. The results emphasize the importance of social media as an effective channel to attract new, international customers. Moreover, this study adds value to the existing literature as well as offers managerial implications.
Keywords: international social media marketing; entrepreneurial marketing; luxury and premium brand; small and medium-sized enterprises; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|